2007
DOI: 10.1093/humrep/dem258
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-mullerian hormone levels and follicular cohort characteristics after pituitary suppression in the late luteal phase with oral contraceptive pills

Abstract: BACKGROUND: Anti-mullerian hormone (AMH) is a marker of ovarian function and reserve and reflects the number and size of antral follicles. The objective of this study was to evaluate the effect of FSH suppression on AMH levels, during the late luteal phase of human menstrual cycle, with the use of oral contraceptives pills (OCP). METHODS: Twenty normovulatory infertile women were included in the study. On the third day of a spontaneous menstrual cycle, the patients were submitted to a transvaginal ultrasound e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 29 publications
3
45
0
4
Order By: Relevance
“…In this respect, various results have been reported regarding the impact of steroid suppression on serum AMH levels. Some studies reported null effect of OCP treatment on serum AMH levels [18,21,22], whereas others revealed suppressed AMH levels in normal cycling women pretreated with OCP [1,15]. In a recent case report it was demonstrated that during 16 week course of menotropin treatment both serum AMH and AFC increased in an IHH patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, various results have been reported regarding the impact of steroid suppression on serum AMH levels. Some studies reported null effect of OCP treatment on serum AMH levels [18,21,22], whereas others revealed suppressed AMH levels in normal cycling women pretreated with OCP [1,15]. In a recent case report it was demonstrated that during 16 week course of menotropin treatment both serum AMH and AFC increased in an IHH patient.…”
Section: Discussionmentioning
confidence: 99%
“…One of most attractive advantages of AMH is that its levels have been shown to be stable under various influences such as hormonal contraception [38,39], GnRH agonist [40], pregnancy [41], and the menstrual cycle [42][43][44][45]. Therefore, measurements can be made anytime during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AMH levels are stable across the menstrual cycle and are not affected by pregnancy or treatment with gonadotropinreleasing hormone agonists. In addition, although an effect of combined oral contraceptive pill on ovarian reserve has been described (Bentzen et al 2012, Deb et al 2012, Kallio et al 2013, its use seems to be associated with minimal suppression of the later FSH-dependent stages of follicle development (Arbo et al 2007, Streuli et al 2008, Sowers et al 2010, Li et al 2011, Shaw et al 2011. It is still debated if clinical and behavioral variables, such as BMI and smoking habit, may influence AMH plasma levels.…”
Section: Amh and Fertilitymentioning
confidence: 99%